Pengaruh Kompensasi dan Kebahagiaan di tempat Kerja Terhadap Kinerja Pegawai PT Industri Kereta Api (Persero) Madiun - Ali, Haider; Nurmayanti, Siti (Postgraduate, University of Mataram, 2024)
This research aims to analyze the influence of Compensation and Happines at work on employee performance at PT Industri Kereta Api (Persero) Madiun. The research method used is a proportional random sampling method with a questionnaire as a data collection instrument. The sample of this study consists of 67 respondents with proportional sampling selected from various departments of the company. Data analysis was conducted using multiple linear regression to test the research hypotheses. The results of the study indicate that compensation has a positive and significantly influence on employee performance, and happiness at work has a positive and significant influence on employee performance. This research contributes to human resource management in PT Industri Kereta Api (Persero) Madiun by providing insights for designing policies that can enhance employee well-being and, in turn, improve overall organizational performance